A Systematic Review for Computer Based Observational Techniques for Assessing Exposure to Risk Factors for Work-Related Musculoskeletal Disorders - Aziana Abdul Rahman, Syahrul; Nasrull Abdol Rahman, Mohd (International Journal of Engineering and Technology, 2018)
The objective of this review are to systematically examine the existing techniques of computer based observational method for assessing Work-related musculoskeletal disorders (WMSDs) and analysed them to the needs of different potential users. Articles related are searched and collected from scientific database starting from 1977 to 2016. Seven methods are identified for computer based observational techniques and from these methods, only three methods have been evaluated as the intra-observer reliability and five methods are evaluated as inter-observer reliability where the average results are moderate to good agreement. For concurrent validity, five methods have been evaluated with moderate agreement. Some of the risk factors that related with WMSDs are; physical, psychosocial, work organization and individual factors. In addition, these existing techniques did not fulfil the criteria of reliability and validity testing during the development of these methods.Â Â